EFFECT OF FOLIAR NUTRITION ON FIG SAPLING GROWTH OF CV. WAZIRY - & Al-bayati, Al-Maamory (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this study was to investigate the effect of foliar nutrition on fig sapling growth of cv. waziry at the College of Agricultural Engineering Scicences A factorial experiment within Randomized Complete Block Design with three replicates was used during the seasons of 2017-2018, using fig seedlings by spraying fertilizers (Foliartal) with four concentrations (0, 2, 4, 6 ml.L-1) and organic fertilizers (Tecamin Max) with four concentrations (0, 3, 4, 5 ml.L-1). Results revealed that application folir of chemical fertilizers caused an increases in plant growth. the highest concentration (4 ml.L-1) was the most effect leading to a significant increases in plant height (19.74, 27.46 cm), stem diameter (3.43, 5.85 mm), leaves area (40.30, 68.47 dm2), and leaves chlorophyll content (219.4, 277.4 mg.100 g-1) The treatment(6 ml.L-1) led to the highest significant increases in nitrogen (2.13, 2.63%), phosphorus (0.86, 0.93%), potassium (2.50, 2.99%) and amino acids (3.77, 6.17% ) for both seasons, respectively Foliar organic fertilizer applied (5 ml.L-1) with amino acid significantly increased plant height (13.39, 19.50 cm), nitrogen (2.11, 2.57%), phosphorus (0.78, 0.81%, potassium (2.90, 2.34%)contents, and the leaves area for the first season (42.65 dm2). While the concentration (4 ml.L-1) indicated a significant increases in stem diameter (3.43, 5.23 mm),leaves chlorophyll content (202.3, 281.2 mg.100 g-1 )fresh weight and amino acid (4.05, 6.26%) for both seasons and leaves area (67.88 dm2) for the second season. the interaction treatments had a significant effect on all the vegetative growth traits .